National Cancer Control Program in Indonesia, Role of Stake Holder - -, Kardinah (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45503347/National-Cancer-Control-Program-in-Indonesia-Role-of-Stake-Holder